Effects of sarcopenia and malnutrition on morbidity and mortality in gynecologic cancer surgery: results of a prospective study. Issue 2 (4th February 2021) - Sehouli, Jalid; Mueller, Kristina; Richter, Rolf; Anker, Markus; Woopen, Hannah; Rasch, Julia; Grabowski, Jacek P.; Prinz‐Theissing, Eva; Inci, Melisa Guelhan
Abstract: Background: Malnutrition and sarcopenia often occur simultaneously in cancer patients and are thought to have harmful effects on both surgical and oncological outcomes. Therefore, we want to evaluate the effects of sarcopenia and malnutrition on severe postoperative complications and overall survival in gynecologic cancer patients. Methods: We assessed nutritional parameters and run a bioelectrical impedance analysis in 226 women. Extracellular mass to body cell mass index, phase angle alpha, muscle mass, and fat mass were evaluated. To determine if patients suffer from sarcopenia, we ran the Timed 'Up and Go' test, performed hand grip strength, and calculated a skeletal muscle index. Postoperative complications were categorized using Clavien–Dindo Classification. Utilizing ROC analysis and logistic regression, we determined predictive clinical factors for severe postoperative complications. Kaplan–Meier method and log‐rank test were used for overall survival analysis. Results: Of the 226 female patients, 120 (53%) had a BMI ≥ 25 kg/m 2, 56 (26%) had a phase angle < 4.75°, and 68 (32%) were sarcopenic according to skeletal muscle index < 27%. Within 30 days after surgery, 40 (18%) patients developed severe postoperative complications, and 4% had died. According to multivariable regression analysis, ECOG status > 1 (OR 4.56, 95% CI: 1.46–14.28, P = 0.009), BMI ≥ 25 kg/m 2 (OR 8.22, 95% CI: 3.01–22.48, P < 0.001), phase angle < 4.75° (OR 3.95, 95% CI: 1.71–9.10, P = 0.001), and tumour stage ≥ III A (OR 3.65, 95% CI: 1.36–9.76, P = 0.01) were predictors of severe postoperative complications. During 59 months of follow‐up, 108 (48%) patients had died. According to multivariable Cox regression ECOG status > 1 (HR 2.51, 95% CI: 1.25–5.03, P = 0.01), hypoalbuminemia (HR 2.15, 95% CI: 1.28–3.59, P = 0.004), phase angle < 4.5° (HR 1.76, 95% CI 1.07–2.90, P = 0.03), tumour stage ≥ III A (HR 2.61, 95% CI: 1.53–4.45, P < 0.001), and severe postoperative complications (HR 2.82, 95% CI: 1.80–4.41, P < 0.001) were predictors of overall mortality. Conclusions: We observed that preoperatively assessed ECOG status > 1, BMI > 25 kg, as well as phase angle alpha < 4.75° and FIGO stage ≥ III A are significantly associated with severe postoperative complications within the first month. Whereas ECOG status > 1, hypoalbuminemia, phase angle < 4.5° as well as FIGO stage ≥ III A and severe postoperative complications within 30 days correlate significantly with poor overall survival.